Yellow Fever Outbreak, Southern Sudan, 2003 - Clayton O. Onyango; Antoinette A. Grobbelaar; Georgina V.F. Gibson; Rosemary C. Sang; Abdourahmane Sow; Robert Swanepoel; Felicity J. Burt (Emerging Infectious Diseases, 2004)
In May 2003, an outbreak of fatal hemorrhagic fever, caused by yellow fever virus, occurred in southern Sudan. Phylogenetic analysis showed that the virus belonged to the East African genotype, which supports the contention that yellow fever is endemic in East Africa with the potential to cause large outbreaks in humans.